The use of word prediction as a tool to accelerate the typing speed and increase the spelling accuracy of primary school children with spelling difficulties - Alant, Erna (University of Pretoria, 2013)
Dissertation (M (Augmentative and Alternative Communication))--University of Pretoria, 2005.